Utilization of Facilities and Infrastructure in the Housing, Settlement and Land Office of Parepare City - Muh. Nasrullah; Eka Wulandari; Jamaluddin Jamaluddin (Journal of Social Science and Economics (JOSSE), 2024)
Office facilities and infrastructure refer to all facilities and infrastructure used in the operation of an office. The purpose of this study is to determine the use of facilities and infrastructure and what factors support and hinder the use of facilities and infrastructure of the Parepare City Housing, Settlement, and Land Office. Therefore, this study has significant in identifying the use of facilities and infrastructure that can lead to an effective and efficient work environment in completing their tasks. Data collection methods include observation, interviews, and documentation. The indicators of the use of facilities and infrastructure in this study are office machinery and equipment that are classified as ineffective because they are not adequate enough in existing availability. Inventory equipment is classified as ineffective due to the completeness of inventory equipment in the office that is still lacking. Office supplies, classified as ineffective because there are damaged / exhausted equipment not in accordance with the estimated time period. Office buildings, classified as effective categories because office buildings already include provisions issued by the local area. Transportation equipment is classified as effective in its utilization because the availability of official vehicles is in accordance with existing Standard Operating Procedures (SOPs). This study presents new information by relating detailed theories and research loci different from previous research on the use of facilities and infrastructure so that it can be used as evaluation material for research loci to advance the use of good and correct facilities and infrastructure.